Blended Learning Assisted Learning as an Effort to Increase Students' Learning Motivation in the New Normal Era - Salma, Salma; Hasan, Hasan; Herlina, Herlina; Misnah, Misnah (Journal of Education Method and Learning Strategy, 2024)
Learning motivation is an important aspect, because low learning motivation has an impact on student learning outcomes. Therefore, learning motivation needs attention and studies are carried out so that teachers can determine the right solution to problems that arise in student learning outcomes. This study aims to determine student motivation during the new normal period in assisted learning with the blended learning model. Covid-19, which has had an impact on the education system, has forced teachers to apply distance learning both offline and online. Entering the new normal era, learning can be done face to face. Therefore, the application of a learning model that combines distance and face-to-face learning can be done proportionally. It is important to understand how student learning motivation is affected by changes in learning from non-face-to-face learning to blended learning. This research was conducted in class V SDN Inpres Silae, Palu City, Central Sulawesi. Using a qualitative approach with a phenomenological design, with a focus on data collection on three things, namely observation, interviews and document study. Data analysis was carried out through three stages, namely data reduction, data presentation, drawing conclusion. The results showed that increasing student motivation in social studies subjects in Class V SDN Inpres Silae, namely evaluators, class managers, mediators and facilitators, and demonstrators. Increasing student motivation in social studies subjects with the help of a blended learning model in class V SD Inpres Silae includes persistence in learning, tenacity in facing difficulties, keen interest and attention in learning, achievement in learning and independence in learning. These findings have been implied to be important in designing learning strategies that are appropriate to the new normal context. Teachers and educational institutions need to pay attention to developing bold and interesting learning experiences, increasing social interaction in face-to-face learning, and providing continuous support to maintain students' learning motivation. In addition, it is also necessary to pay attention to the flexibility of space and time in learning so that students can take full advantage of their potential.